Chemical Characterization of Taif Rose (Rosa damascena Mill var. trigentipetala) Waste Methanolic Extract and Its Hepatoprotective and Antioxidant Effects against Cadmium Chloride (CdCl2)-Induced Hepatotoxicity and Potential Anticancer Activities against Liver Cancer Cells (HepG2) - Reham Z. Hamza; Hatim M. Al-Yasi; Esmat F. Ali; Mustafa A. Fawzy; Tharwat G. Abdelkader; Tarek M. Galal (Crystals, 2022)
Taif rose (Rosa damascena Mill) is one of the most important economic products of the Taif Governorate, Saudi Arabia. Cadmium chloride (CdCl2) is a common environmental pollutant that is widely used in industries and essentially induces many toxicities, including hepatotoxicity. In this study, the major compounds in the waste of Taif rose extract (WTR) were identified and chemically and biologically evaluated. GC–MS analysis of WTR indicated the presence of many saturated fatty acids, vitamin E, triterpene, dicarboxylic acid, terpene, linoleic acid, diterpenoid, monoterpenoid, flavonoids, phenylpyrazoles, and calcifediol (vitamin D derivative). The assessment of potential anticancer activity against HepG2 cells proved that WTR had a high cell killing effect with IC50 of 100–150 µg/mL. In addition, WTR successfully induced high cell cycle arrest at G0/G1, S, and G2 phases, significant apoptosis, necrosis, and increased autophagic cell death response in the HepG2 line. For the evaluation of its anti-CdCl2 toxicity, 32 male rats were allocated to four groups: control, CdCl2, WTR, and CdCl2 plus WTR. Hepatic functions and antioxidant biomarkers (SOD, CAT, GRx, GPx, and MDA) were examined. Histological changes and TEM variations in the liver were also investigated to indicate liver status. The results proved that WTR alleviated CdCl2 hepatotoxicity by improving all hepatic vitality markers. In conclusion, WTR could be used as a preventive and therapeutic natural agent for the inhibition of hepatic diseases and the improvement of redox status. Additional in vitro and in vivo studies are warranted.